Cultural Arguments Against Offensive Speech in Malaysia: Debates Between Liberalism and Asian Values on Pornography and Hate Speech - Sani, Mohd Azizuddin Mohd (Richtmann Publishing, 2011)
This article is about analysing two issues of pornography and hate speech in the context of political theory and Malaysianpolitics. This article examines both issues from liberals arguments and it shows that although liberalism supports the right for free speech,since the 1970s many liberals feel that pornography and hate speech should not be part of free speech doctrine because both are notcontributing for the public good in democratic system and they are also detrimental to the society. By using the cultural arguments ofAsian values, Malaysia totally rejects these practices because they are not suitable in a cultural and religious conscious Malaysianmultiracial society. Although many are sceptic about the use of Asian values for the rejection and the uses of hate speech by peopleincluding the government, opposition and NGOs for political gain, in principle, Malaysians are in consensus of rejecting both issues forthe good of society.